2012
DOI: 10.1007/s00382-012-1371-7
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation variability during the past 400 years in the Xiaolong Mountain (central China) inferred from tree rings

Abstract: We developed the first tree-ring chronology, based on 73 cores from 29 Pinus tabulaeformis trees, for the Xiaolong Mountain area of central China, a region at the boundary of the Asian summer monsoon. This chronology exhibits significant (at 0.01 level) positive correlations with precipitation in May and June, and negative correlations with temperature in May, June and July. Highest linear correlation is observed between tree growth and the seasonalized (April-July) precipitation, suggesting that tree rings te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 46 publications
4
34
0
Order By: Relevance
“…This period coincides with a weakened Asian summer monsoon [40], which is the main source of precipitation in the study area. Moreover, the temperatures during this period are greater than or equal to those in the 20 th century.…”
Section: Resultsmentioning
confidence: 68%
“…This period coincides with a weakened Asian summer monsoon [40], which is the main source of precipitation in the study area. Moreover, the temperatures during this period are greater than or equal to those in the 20 th century.…”
Section: Resultsmentioning
confidence: 68%
“…Li et al (2006) suggested that drought variability has a 2-to 3-year cycle in the central Tien Shan area of northwestern China. The 2-to 3-year cycle precipitation variability in southern Kazakhstan has been widely documented in previous tree-ring-based climate reconstructions (Fang et al, 2010(Fang et al, , 2012 and may be related to the tropospheric biennial oscillation (Meehl, 1987). The spectral peaks separated by 5-7 years fall within the spectral bandwidth of the El Niño-Southern Oscillation (Allan et al, 1996).…”
Section: Precipitation Variability In the Past 250 Yearsmentioning
confidence: 86%
“…The coniferous species growing in extremely stressed environments such as cold and arid conditions, i.e., Sabina przewalskii, often exhibit small rings during most of their lifetimes (Shao et al, 2010;. Other tree species growing in moderately stressed environments, such as P. tabuliformis (Fang et al, 2012b) and P. massoniana , often have moderate growth values. P. taiwanensis and P. tabuliformis were not distinguished from each other before the 1930s owing to their similar ecological features (Wu, 2004), which may suggest the close genetic relationships between them.…”
Section: Tree-growth Patternmentioning
confidence: 99%